Feasibility, user satisfaction, and knowledge improvement after a VR training program for healthcare professionals managing behavioral and psychological symptoms of dementia (BPSD): Protocol for the FORMSPC-REALVI single-arm pre-post study. - Hermine Lenoir; Maribel Pino; Sébastien Dacunha; Anne-Sophie Rigaud (PLoS ONE)
Background Behavioral and psychological symptoms are a common challenge for healthcare professionals when managing patients with dementia, and effective verbal and nonverbal communication skills are crucial in caring for such patients. Objectives This article describes a research study protocol for investigating the effectiveness of a virtual reality (VR) training program for healthcare professionals in managing disruptive behavioral and psychological symptoms of dementia (BPSD), such as aggressiveness, agitation, and care refusal. Methods The training scenarios were co-designed with ten healthcare professionals and implemented using an immersive 3D VR platform. Forty geriatric healthcare professionals will participate in a 2-hour training session using VR movies and a Moodle-based theoretical reinforcement. Before and after the training, participants will complete self-assessment questionnaires and knowledge-based quizzes designed to evaluate their perceived competence and understanding of appropriate communication strategies with patients displaying BPSD. The primary outcome will be the change in quiz scores between the pre- and post-training evaluations. Secondary outcomes include training satisfaction, perceived competence, and system usability. Hypotheses Trial registration This study is registered in the French General Data Protection Regulation (GDPR) registry of Assistance Publique - Hôpitaux de Paris (N° 2022 0518135339-18 May 2022). As the trial targets health-providers and measures effects only on them (and not on providers' patients), clinical trial registration is not required (see ICMJE guidelines: https://www.icmje.org/about-icmje/faqs/clinical-trials-registration/).